Brain and muscle nicotinic acetylcholine receptors are different but homologous proteins. - Conti-Tronconi, B M (1985)
An alpha-bungarotoxin-binding protein was purified from chick optic lobe and brain by an improved method. Previous and present observations justify its designation as a brain nicotinic acetylcholine receptor (AcChoR). It contains subunits whose apparent molecular weights are somewhat larger than those of subunits of peripheral AcChoRs. The size of the optic lobe AcChoR complex is greater than that of the peripheral receptor when estimated from its sedimentation behavior. Brain AcChoR subunits can be specifically precipitated by a monoclonal antibody directed against chick muscle AcChoR. Amino-terminal amino acid sequence analysis was performed on AcChoR preparations and isolated subunits from the optic lobe and from the rest of the chick brain. The sequences obtained demonstrate that, at least for the lowest molecular weight component, the AcChoRs from different brain areas are identical and they are highly homologous to muscle AcChoR. It is concluded that the brain alpha-bungarotoxin-binding protein is indeed a nicotinic AcChoR and is encoded by a set of genes that is different from, but strongly related to, that for the muscle AcChoR.